PNEUMONIA AS A PRIMARY MANIFESTATION OF INFECTIVE ENDOCARDITIS - CASE REPORT - Milosavljevikj, Ane; Milenkovikj, Zvonko; Cvetanovska, Marija; Janeku-Kartalova, Marija (Journal of Morphological Sciences; Vol 7 No 2 (2024): JMS, 2024)
This case report discusses the clinical presentation, diagnostic challenges, and clinical implications of a patient initially hospitalized for pneumonia, later diagnosed with infective endocarditis with negative blood cultures. A 72-year-old female presented with a 3-day history of general infection symptoms and a chest X-ray indicative of right-sided pneumonia. The patient did not respond adequately to standard antimicrobial therapy, prompting further diagnostic investigation. A computed tomography scan of the chest revealed a suspected thrombus in the left atrium. Echocardiography confirmed vegetation on the posterior mitral leaflet. Blood cultures and serological tests were negative. Follow-up echocardiography showed progression of the vegetation with compromised mitral valve function, necessitating surgical intervention, and the patient was transferred to the Cardiac Surgery Clinic. The case emphasizes the importance of timely recognition of infective endocarditis, even when patients initially present with respiratory symptoms. The diagnostic protocol includes echocardiographic methods for detecting valve vegetations. Negative blood cultures do not rule out endocarditis. Rapid diagnosis is crucial, as surgical intervention is often indicated, and failure to diagnose can have fatal consequences. Keywords: infective endocarditis, pneumonia, echocardiography, blood culture